A politics of patent law : crafting the participatory patent bargain - Murray, Kali N., 1975- (Routledge, 2013)
"There has been much written on the impact of the international treaties like the Trade Related Aspects on Intellectual Property (TRIPS), which lament the failure of patent systems to respond to the interests of a diverse set of non-profit, public interest, and non-corporate entities. But these studies have failed to examine why such inclusion has proven to be particularly difficult. This book examines how patent law can accommodate what James Boyle terms a "politics" that is a conceptual map of issues, a rough working model of costs and benefits, and a functioning coalition-politics of groups unified by common interest perceived in apparently diverse situations. A Politics of Patent Law surveys national statutory and case law, regional patent treaties, and international treaties, to understand how to craft a more "participatory bargain" in patent law. The book provides a substantive account about the ways in which the various types of participatory mechanisms currently operate, and examines how participatory mechanisms can be developed in patent law, particularly within the regional and international context. The book will set out a "tool-box" of participatory mechanisms which would allow for, and foster third party participation in the patent process"--Vydavatelská anotace
Keywords: patentové právo; patent laws and legislation; monografie; monographs